Integrative metabolomic and network pharmacological analysis reveals potential mechanisms of Cardamine circaeoides Hook.f. & Thomson in alleviating potassium oxonate-induced asymptomatic hyperuricemia in rats - Zhu, Yingli; Di, Songrui; Li, Yipeng; Liang, Weican; Liu, Jinlian; Nuermaimaiti, Reyisai; Fei, Wenting; Wang, Chun; Wang, Linyuan; Zhang, Jianjun (Frontiers in Pharmacology, 2023)
Cardamine circaeoides Hook.f. & Thomson (CC), a herb of the genus Cardamine (family Brassicaceae), has a rich historical usage in China for both culinary and medicinal purposes. It is distinguished by its remarkable ability to hyperaccumulate selenium (Se). CC has demonstrated efficacy in the prevention of metabolic disorders. However, investigations into the effects of CC on asymptomatic hyperuricemia remain scarce. The objective of this study is to elucidate mechanism by which CC aqueous extract (CCE) exerts its anti-hyperuricemic effects on asymptomatic hyperuricemic rats induced by potassium oxonate (PO) by integrating metabolomics and network pharmacological analysis. Asymptomatic hyperuricemia was induced by feeding rats with PO (1000mg/kg) and CCE (0.75, 1.5, or 3 mg/kg) once daily for 30 days. Various parameters, including body weight, uric acid (UA) levels, histopathology of renal tissue and inflammatory factors (IL-1β, IL-6, IL-8 and TNF-α) were assessed. Subsequently, metabolomic analysis of kidney tissues was conducted to explore the effects of CCE on renal metabolites and the related pathways. Furthermore, network pharmacology was employed to explicate the mechanism of action of CCE components identified through UPLC-Q-TOF-MS analysis. Finally, metabolomic and network-pharmacology analyses were performed to predict crucial genes dysregulated in the disease model and rescued by CVE, which were then subjected to verification by RT-qPCR. The findings revealed that CCE significantly inhibited the UA levels from the 21st day to the 30th day. Moreover, CCE exhibited significant inhibition of IL-1β, IL-6, IL-8 and TNF-α levels in renal tissues. Dysregulation of 18 metabolites and the tyrosine, pyrimidine, cysteine and methionine, sphingolipid, and histidine metabolism pathways was prevented by CCE treatment. A joint analysis of targets predicted using the network pharmacology approach and the differential metabolites found in metabolics predicted 8 genes as potential targets of CCE and three of them (PNP gene, JUN gene, and ADA gene) were verified at the mRNA level by RT-qPCR. We conclude that CCE has anti-hyperuricemia effects and alleviates renal inflammation in a rat model of hyperuricemia, and these efficacies are associated with reversal of increased ADA, PNP and JUN mRNA expression in renal tissues.